1988
DOI: 10.1128/mcb.8.4.1525
|View full text |Cite
|
Sign up to set email alerts
|

Double minute chromosomes can be produced from precursors derived from a chromosomal deletion.

Abstract: Recent experiments have shown that gene amplification can be mediated by submicroscopic, autonomously replicating, circular extrachromosomal molecules. We refer to those molecules as episomes (S. Carroll, P. Gaudray, M. L. DeRose, J. F. Emery, J. L. Meinkoth, E. Nakkim, M. Subler, D. D. Von Hoff, and G. M. Wahl, Mol. Cell. Biol. 7:1740-1750. The experiments reported in this paper explore the way episomes are formed and their fate in the cell over time. The data reveal that in our system the episomes are initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
157
0
1

Year Published

1992
1992
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(169 citation statements)
references
References 49 publications
11
157
0
1
Order By: Relevance
“…1a,b and Table 1). Similar deletions associated with amplification of MYC on dmin chromosomes or episomes have been reported 12 .…”
supporting
confidence: 73%
“…1a,b and Table 1). Similar deletions associated with amplification of MYC on dmin chromosomes or episomes have been reported 12 .…”
supporting
confidence: 73%
“…In addition, in vitro studies imply that many of the structural chromosomal abnormalities occurring in tumors and tumorigenic cell lines (Bishop, 1987;Tlsty et al, 1989) may result from molecular mechanisms common to those mediating extrachromosomal gene amplification. For example, recent studies have provided firm evidence that some extrachromosomal elements have the potential to integrate into chromosomes, resulting in either HSRs, ECRs (Carroll et al, 1988;Ruiz and Wahl, 1990;Von Hoff et al, 1990;Windle et al, 1991), or other chromosome abnormalities such as ring chromosomes (Windle et al, 1991). These studies support earlier observations of gene amplification in hamster cell lines in which Biedler (1982) observed that the extrachromosomal circular DMs rapidly integrated into chromosomes, resulting in HSR structures (Biedler, 1982).…”
Section: Introductionmentioning
confidence: 52%
“…Amplification of a region of DNA via an extrachromosomal element often results in a deletion at the corresponding chromosomal locus (Carroll et al, 1988;Hunt et al, 1990;Heard et al, 1991). If a deletion is present, its respective size could provide information as to the size of the initial amplicon.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies led to the identification of at least two different initial gene amplification mechanisms (Coquelle et al, 1997;Carroll et al, 1988;Ma et al, 1993;Ruiz and Wahl, 1988;Smith et al, 1992;Toledo et al, 1992Toledo et al, , 1993Trask and Hamlin, 1989;Windle et al, 1991). The breakage-fusion-bridge (BFB) cycle mechanism, first described by McClintock (1942), accumulates copies organized as large inverted repeats on a chromosome arm where one normal gene copy maps in non-amplified cells (Coquelle et al, 1997;Ma et al, 1993;Toledo et al, 1992Toledo et al, , 1993.…”
Section: Introductionmentioning
confidence: 99%